MEMAHAMI EKOLOGI HINDU MELALUI AJARAN TRI HITHA KARANA - Dewa Ketut Hendra Puspawan (Sanjiwani: Jurnal Filsafat, 2018)
God created the universe and its contents is for the benefit of all beings present in nature, especially humans because man is the supreme being who is given the mind, the mind to utilize this world wisely for the sake of the need and the sustainability of life for all beings. Man, nature and environment are a perfect unity of God’s created ecosystem, interdependence among each other is a natural cycle. Hinduism since ancient times has participated in maintaining balance among other living things. The study was designed with a qualitative approach to obtain discoveries that could not be achieved by using statistical procedures or other means of quantification. All forms of disasters and calamities that occur can not necessarily be avoided, but we as human beings who think can still reduce the disaster if we are conscious and able to maintain the environment well, and contribute in the form of mind, action to reduce the greed of natural exploitation in an effort equating nature and other creatures, in order to preserve the natural ecology.